Were surgical outcomes for acute appendicitis impacted by the COVID-19 pandemic? - Rachel Waldman; Harrison Kaplan; I. Michael Leitman (BMC Surgery, 2023)
Abstract Background The COVID-19 pandemic disrupted healthcare systems throughout the world. We examine whether appendectomy outcomes in 2020 and 2021 were affected by the pandemic. Methods We conducted a retrospective cohort study of 30-day appendectomy outcomes using the ACS-NSQIP database from 2019 through 2021. Logistic regression and linear regression analyses were performed to create models of post-operative outcomes. Results There were no associations between the time period of surgery and death, readmission, reoperation, deep incisional SSI, organ space SSI, sepsis, septic shock, rate of complicated appendicitis, failure to wean from the ventilator, or days from admission to operation. During the first 21 months of the pandemic (April 2020 through December 2021), there was a decreased length of hospital stay (p = 0.016), increased operative time (p < 0.001), and increased likelihood of laparoscopic versus open surgery (p < 0.001) in compared to 2019. Conclusions There were minimal differences in emergent appendectomy outcomes during the first 21 months of the pandemic when compared to 2019. Surgical systems in the US successfully adapted to the challenges presented by the COVID-19 pandemic.